Urban Chinese governance, contention, and social control in the new millennium - Hurst, William, 1975- (Rethinking socialism and reform in China, 2019)
"Bringing together a wide range of leading experts across several disciplines, this book offers critical insights on some of the most important questions of contemporary urban Chinese politics and society. Drawing on extensive research across different localities and issues in China, the chapters offer rich data and fresh analyses of the shifting contours of urban governance, social mobilization and contention, and the mechanisms of social control in the new Millennium. Taken together, this collection represents the most comprehensive look in some years at how urban Chinese political institutions have adapted and responded to challenges and how social actors and groups have mobilized to press for redress of substantial new grievances"--